The Influence of Taekwondo Movement Activities on The Cognitive Function Of Early Childhood At The Fundamental Stage - Febriani, Nawang Wulan; Nurjaya, Dede Rohmat; Kusumah, Widi; Mulyana (Universitas Negeri Semarang, 2024)
Children's cognitive development is a crucial part of their growth process, particularly in the areas of comprehension and memory. However, many children struggle to improve this ability. Exercise activities such as taekwondo are thought to be able to enhance cognitive development, although there have been few studies specifically looking at their benefits for Indonesian children. The purpose of this study is to evaluate the effects of taekwondo-related activities on cognitive functions, particularly concentration, in children aged 6 to 9 years in the elementary stage. This study uses an experimental approach with 20 children from Sukabumi Academy Taekwondo Dojang, consisting of 10 children and 10 adults. Taekwondo exercises are performed three times a month for 21 minutes at moderate intensity (between 50-80%). The Stroop Colour Word Test (SCWT) is an instrument for assessing a person's ability to understand words, colours and word combinations. The paired T-test is used to analyse the differences between the results before and after the test. The results show a significant increase in the following three variables: Word-Colour Combination (t(19) = 10.491, p<0.001), Word-Colour Recognition (t(19) = 7.973, p<0.001) and Colour-Colour Recognition (t(19) = 8.063, p<0.001). The average score after the test was better than before the test, indicating an increase in concentration after the Taekwondo intervention. Taekwondo exercises significantly improve cognitive functions, especially concentration, in children aged 6 to 9 years. This study highlights the importance of incorporating sports such as taekwondo into early childhood education and development programmes.